2011
DOI: 10.1063/1.3560062
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cycle terahertz pulses with amplitudes exceeding 1 MV/cm generated by optical rectification in LiNbO3

Abstract: Using the tilted-pump-pulse-front scheme, we generate single-cycle terahertz ͑THz͒ pulses by optical rectification of femtosecond laser pulses in LiNbO 3 . In our THz generation setup, the condition that the image of the grating coincides with the tilted-optical-pulse front is fulfilled to obtain optimal THz beam characteristics and pump-to-THz conversion efficiency. By using an uncooled microbolometer-array THz camera, it is found that the THz beam leaving the output face of the LN crystal can be regarded as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
515
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 786 publications
(525 citation statements)
references
References 21 publications
7
515
0
3
Order By: Relevance
“…Although the former has been ahead in terms of intensity, the availability and versatility of lasers are dominating time-resolved THz high-field science. The most prominent techniques for intense THz pulse generation, by employing a femtosecond amplified laser pulse, are based on laser-driven ion acceleration 16 , emission from a gas plasma 17 and optical rectification in inorganic (for example, LiNbO 3 ) 18 and organic nonlinear crystals (for example, 2-(3-(4-hydroxystyryl)-5,5-dimethylcyclohex-2-enylidene)malononitrile) (OH1), 4-N,N-dimethylamino-4 0 -N 0 -methyl-stilbazolium tosylate (DAST), 4-N,N-dimethylamino-4 0 -N 0 -methyl-stilbazolium 2,4,6-trimethylbenzenesulfonate (DSTMS)) [19][20][21] . So far, the peak fields from these systems have been limited to 0.12-0.5 GV m À 1 .…”
mentioning
confidence: 99%
“…Although the former has been ahead in terms of intensity, the availability and versatility of lasers are dominating time-resolved THz high-field science. The most prominent techniques for intense THz pulse generation, by employing a femtosecond amplified laser pulse, are based on laser-driven ion acceleration 16 , emission from a gas plasma 17 and optical rectification in inorganic (for example, LiNbO 3 ) 18 and organic nonlinear crystals (for example, 2-(3-(4-hydroxystyryl)-5,5-dimethylcyclohex-2-enylidene)malononitrile) (OH1), 4-N,N-dimethylamino-4 0 -N 0 -methyl-stilbazolium tosylate (DAST), 4-N,N-dimethylamino-4 0 -N 0 -methyl-stilbazolium 2,4,6-trimethylbenzenesulfonate (DSTMS)) [19][20][21] . So far, the peak fields from these systems have been limited to 0.12-0.5 GV m À 1 .…”
mentioning
confidence: 99%
“…THz pulses were generated by optical rectification of femtosecond laser pulses in a LiNbO 3 crystal by using the tilted-pump-pulse-front scheme. [13][14][15] An amplified Ti:sapphire laser (repetition rate 1 kHz, central wavelength 780 nm, pulse duration 100 fs, and 4 mJ/pulse) was used for the light source. As shown in the inset of Fig.…”
mentioning
confidence: 99%
“…(1) (2) where m is the diffraction order, λ p is the pump wavelength, d is the grating groove number, is the group index of the pump pulse,   and   are the magnification factors of the lens for the pump wave front and the grating image, respectively, and   is the diffraction angle [16]. To optimize the efficiency of THz pulse generation, we chose two magnification factors (     ≈ ) and the diffraction angle (   °) by using the Eqs.…”
Section: Design Of Efficient Phase Matching By Tilted Pulse-frontmentioning
confidence: 99%
“…However, the large index dispersion and mismatch in LiNbO3 inhibit efficient phase matching in a collinear geometry. Since Hebling et al suggested a non-collinear phase matching in a prism-cut LiNbO3 using a tilted pulse-front pumping (TPFP) scheme and reported its proof-of-principle experiment for efficient THz pulse generation in 2003, many efforts have followed to improve both THz pulse energy and spectral bandwidth by utilizing different configurations and excitation sources [15][16][17]. As a result, it turned out that there was a tradeoff between the pump-to-THz conversion efficiency and the spectral bandwidth for THz pulse generation.…”
Section: Introductionmentioning
confidence: 99%